Reduced Simian Immunodeficiency Virus Replication in Macrophages of Sooty Mangabeys Is Associated with Increased Expression of Host Restriction Factors - Mir, Kiran D. (J Virol, 2015)
Macrophages are target cells of HIV/SIV infection that may play a role in AIDS pathogenesis and contribute to the long-lived reservoir of latently infected cells during antiretroviral therapy (ART). In previous work, we and others have shown that during pathogenic SIV infection of rhesus macaques (RMs), rapid disease progression is associated with high levels of in vivo macrophage infection. In contrast, during nonpathogenic SIV infection of sooty mangabeys (SMs), neither spontaneous nor experimental CD4(+) T cell depletion results in substantial levels of in vivo macrophage infection. To test the hypothesis that SM macrophages are intrinsically more resistant to SIV infection than RM macrophages, we undertook an in vitro comparative assessment of monocyte-derived macrophages (MDMs) from both nonhuman primate species. Using the primary isolate SIV(M949), which replicates well in lymphocytes from both RMs and SMs, we found that infection of RM macrophages resulted in persistent SIV-RNA production while SIV-RNA levels in SM macrophage cultures decreased 10- to 100-fold over a similar temporal course of in vitro infection. To explore potential mechanisms responsible for the lower levels of SIV replication and/or production in macrophages from SMs we comparatively assessed, in the two studied species, the expression of the SIV coreceptor as well as the expression of a number of host restriction factors. While previous studies showed that SM monocytes express lower levels of CCR5 (but not CD4) than RM monocytes, the level of CCR5 expression in MDMs was similar in the two species. Interestingly, we found that SM macrophages exhibited a significantly greater increase in the expression of tetherin (P = 0.003) and TRIM22 (P = 0.0006) in response to alpha interferon stimulation and increased expression of multiple host restriction factors in response to lipopolysaccharide stimulation and exposure to SIV. Overall, these findings confirm, in an in vitro infection system, that SM macrophages are relatively more resistant to SIV infection compared to RM macrophages, and suggest that a combination of entry and postentry restriction mechanisms may protect these cells from productive SIV infection. IMPORTANCE This manuscript represents the first in vivo comparative analysis of monocyte-derived macrophages (MDMs) between rhesus macaques, i.e., experimental SIV hosts in which the infection is pathogenic and macrophages can be infected, and sooty mangabeys, i.e., natural SIV hosts in which the infection is nonpathogenic and macrophages are virtually never infected in vivo. This study demonstrates that mangabey-derived MDMs are more resistant to SIV infection in vitro compared to macaque-derived MDMs, and provides a potential explanation for this observation by showing increased expression of specific retrovirus restriction factors in mangabey-derived macrophages. Overall, this study is important as it contributes to our understanding of why SIV infection is nonpathogenic in sooty mangabeys while it is pathogenic in macaques, and is consistent with a pathogenic role for in vivo macrophage infection during pathogenic lentiviral infection.